A decade of genomic history for healthcare-associated Enterococcus faecium in the United Kingdom and Ireland - Raven, Kathy E. (Genome Res, 2016)
Vancomycin-resistant Enterococcus faecium (VREfm) is an important cause of healthcare-associated infections worldwide. We undertook whole-genome sequencing (WGS) of 495 E. faecium bloodstream isolates from 2001–2011 in the United Kingdom and Ireland (UK&I) and 11 E. faecium isolates from a reference collection. Comparison between WGS and multilocus sequence typing (MLST) identified major discrepancies for 17% of isolates, with multiple instances of the same sequence type (ST) being located in genetically distant positions in the WGS tree. This confirms that WGS is superior to MLST for evolutionary analyses and is more accurate than current typing methods used during outbreak investigations. E. faecium has been categorized as belonging to three clades (Clades A1, hospital-associated; A2, animal-associated; and B, community-associated). Phylogenetic analysis of our isolates replicated the distinction between Clade A (97% of isolates) and Clade B but did not support the subdivision of Clade A into Clade A1 and A2. Phylogeographic analyses revealed that Clade A had been introduced multiple times into each hospital referral network or country, indicating frequent movement of E. faecium between regions that rarely share hospital patients. Numerous genetic clusters contained highly related vanA-positive and -negative E. faecium, which implies that control of vancomycin-resistant enterococci (VRE) in hospitals also requires consideration of vancomycin-susceptible E. faecium. Our findings reveal the evolution and dissemination of hospital-associated E. faecium in the UK&I and provide evidence for WGS as an instrument for infection control.